The genetics of functional disability in schizophrenia and bipolar illness: Methods and initial results for VA cooperative study #572. Issue 4 (5th May 2014) - Harvey, Philip D.; Siever, Larry J.; Huang, Grant D.; Muralidhar, Sumitra; Zhao, Hongyu; Miller, Perry; Aslan, Mihaela; Mane, Shrikant; McNamara, Margaret; Gleason, Theresa; Brophy, Mary; Przygodszki, Ronald; et al.
<x xml:space="preserve">Abstract</x> Given the prominence of cognitive impairments and disability associated with schizophrenia and bipolar disorder, substantial interest has arisen in identifying determinants of the diseases and their features. Genetic variation has been linked to skills that underlie disability ("functional capacity" or FC), highlighting need for understanding of these relationships. We describe the design and methods of a large, multisite, observational study focusing on the genetics of functional disability in schizophrenia and bipolar disorder, presenting initial data on recruitment, and characterization of the sample. Known as Veterans Affairs (VA) Cooperative Studies Program (CSP)#572, this study is recruiting, diagnosing, and assessing U.S. Veterans with either schizophrenia or bipolar I disorder. Assessments include neuropsychological (NP) testing, FC, suicidality, and co‐morbid conditions such as posttraumatic stress disorder (PTSD). A sample of "psychiatrically healthy" Veterans from another project serves as a comparison group. An interim total of 8, 140 participants (42.1% schizophrenia) have been recruited and assessed as of September 30, 2013, with 9 months of enrollment remaining and with a target sample size of 9, 500. Veterans with schizophrenia were more likely to never have married, whereas lifetime PTSD and suicidality were more common in the bipolar veterans. Performance on the FC measures and NP tests was consistent with previous results, with mean t‐scores of 35 (−1.5 SD) for schizophrenia and 41 (−0.9 SD) for the bipolar Veterans. This large population is representative of previous studies in terms of patient performance and co‐morbidities. Subsequent genomic analyses will examine the genomic correlates of performance‐based measures. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.